Isoprenoid Synthesis in Plants and Microorganisms New Concepts and Experimental Approaches - Bach, Thomas J.; Rohmer, Michel; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Isoprenoids are important in primary and secondary metabolism. They have implications in a myriad of physiological processes notably in plants, microorganisms and parasites, and biological activities at the cellular, organism, and ecosystem levels. The importance of isoprenoids in various areas of the scientific world has spurred intense research worldwide. Also their role in "nutraceuticals" has stimulated scientific curiosity. Literature on isoprenoids is widely scattered in journals with quite differing readerships and geographic distribution. A comprehensive book on isoprenoids does not exist. Isoprenoid Synthesis in Plants and Microorganisms: New Concepts and Experimental Approaches fills this gap by presenting the latest and the most applicable information on isoprenoids. The most recent TERPNET conference serves as the backdrop and provides much of the inspiration for the topics covered in the book. Additional topics of interest are covered as well, making Isoprenoid Synthesis in Plants and Microorganisms: New Concepts and Experimental Approaches the most comprehensive review of isoprenoid synthesis to date.
Isoprenoid Bbiosynthesis in Pprokaryotic Organisms -- 1-deoxy-D-xylulose 5-phosphate Synthase (DXS), A Crucial Enzyme for Isoprenoids Biosynthesis -- Biosynthetic Genes and Enzymes of Isoprenoids Produced by Actinomycetes -- Interactions of Isoprenoid Pathway Enzymes and Indirect Stimulation of Isoprenoid Biosynthesis by Pentose Phosphate Cycle Substrates in Synechocystis PCC 6803 -- Metabolic Engineering of Monoterpenoids Production in Yeast -- Metabolic Engineering of Isoprenoid Production: Reconstruction of Multistep Heterologous Pathways in Tractable Hosts -- Microbially-Derived Semi-synthetic Artemisinin -- Artemisinin: Controlling its Production in Artemisia Annua -- Fosmidomycin as an Antimalarial Agent -- Regulation of Isoprene and Monoterpene Emission -- Involvement of Compartmentalization in Monoterpene and Sesquiterpene Biosynthesis in Plants -- Strategies for the Manipulation of Carbocations by Aristolochene Synthase -- Elucidating the Formation of Geranyllinalool, the Precursor of the Volatile C16-homoterpene TMTT Involved in Indirect Plant Defense -- Strigolactones: A Cry for Help Results in Fatal Attraction. Is Escape Possible? -- Prenyldiphosphate Synthases and Gibberellin Biosynthesis -- Gibberellin Phytohormone Metabolism -- Control of Plastidial Isoprenoid Precursor Supply: Divergent 1-deoxy-D-xylulose 5-phosphate Synthase (DXS) Isogenes Regulate the Allocation to Primary or Secondary Metabolism -- Tobacco Trichomes as a Platform for Terpenoid Biosynthesis Engineering -- Prenylated Proteins are Required for Methyl jasmonate-induced Monoterpenoid Indole Alkaloids Biosynthesis in Catharanthus roseus -- The Role of Prenylcysteine Methylation and Metabolism in Abscisic Acid Signaling in Arabidopsis Thaliana -- What We Do and Do Not Know About the Cellular Functions of Polyisoprenoids -- Regulation of 3-hydroxy-3-methylglutaryl-CoA Synthase and 3-hydroxy-3-methylglutaryl-CoA Reductase and Rubber Biosynthesis of Hevea brasiliensis (B.H.K.) Mull. Arg -- Development of Crops to Produce Industrially Useful Natural Rubber -- Occurrence in Tobacco of Two Acetoacetyl-Coenzyme A Thiolases with Distinct Expression Patterns and Subcellular Localization -- The Sterol C4-Demethylation in Higher Plants -- Sterol C22-desaturase and its Biological Roles -- Enzymatic Synthesis of Unnatural Cyclic Triterpenes -- Saponin Synthesis and Function -- Cardenolide Aglycone Formation in Digitalis -- Biosynthesis of Isoprenoid Precursors in Arabidopsis -- Understanding the Mechanisms that Modulate the MEP Pathway in Higher Plants -- Functional Analysis of HMG-CoA Reductase and Oxidosqualene Cyclases in Arabidopsis -- Systems Understanding of Isoprenoid Pathway Regulation in Arabidopsis.
Keywords: Plant science; Botany; Plant biochemistry; Plant pathology; Microbiology; Plant physiology; Animal physiology; Plant Sciences; Plant Biochemistry; Plant Pathology; Microbiology; Plant Physiology; Animal Physiology